Kinerja KUA dalam Pencatatan Perkawinan Sejenis - Syaidatur Rosidah Alawiyah; Khofifah Lutfia Effendi; Zakiyatul Ulya (Fakultas Syariah IAIN Madura, 2024)
This paper is motivated by the emergence of news of same-sex marriages that are officially registered at the KUA, causing pros and cons in the community. This study aims to determine the effectiveness of the KUA's role in the practice of recording same-sex marriage in terms of Lawrence M. Friedman's theory of legal effectiveness. This research uses a qualitative approach and data collection using documentation techniques. The results showed that the role of the KUA was not effective according to the theory of legal effectiveness by Friedman M. Lawrence, because the elements of legal culture and legal structure could not run optimally. In the implementation of this legal structure, there is an element of negligence committed by the KUA in carrying out its duties as an authorized institution to carry out marriage registration, which in this case is evidenced by the non-optimal implementation of the document examination stage which results in the recording of same-sex marriages. Meanwhile, in legal culture, the perpetrators have a low level of legal awareness. This is evidenced by their actions to falsify their identity in order to realize their personal desires which are not in accordance with legal and social norms in Indonesia.)